Hubungan Kesejahteraan Psikologis dengan Stres pada Mahasiswa Tingkat Akhir selama masa Pandemi Covid - Yustika, Dewani; Rahmawati, Arni Nur; Putri, Noor Rochmah Ida Ayu Trisno; Dewi, Feti Kumala (Poltekkes Kemenkes Kendari, 2021)
Final year students will experience an increase in stress, especially in the process of writing a thesis. However, the stress can decrease when the student's welfare is in the high category. The purpose of this study was to analyze the relationship between psychological well-being and stress in final year students. This study used a cross sectional design for 61 regular final students, namely Bachelor of Nursing and Bachelor of Pharmacy. Primary data were taken using the Scales of Psychological Well-being (SPWB) and the Depression Anxiety and Stress Scale (DASS-14). The results of the bivariate analysis showed that there was a low relationship between psychological well-being and stress in final year students with a negative relationship direction (r=-.255; p=0.047).